Distributed authentication for the Western Australian University Libraries - Green, Peter (Victorian Association for Library Automation, 2004)
The need to establish a means of achieving reliable, automated inter-institutional authentication was identified by the Western Australian Group of University Librarians (WAGUL) in 1999 as a strategic priority and a project was subsequently established as a result of a substantial grant from the Commonwealth Development Pool (CDP). The WAGUL Authentication Project (WALAP) first reported on its progress at VALA 2002 and now follows up with a report on the achievements to date and the challenges to come.